Depiction of a hero embarked on an expedition on a hero stone - Temples of India Project Team (Jio Institute, 2024)
The topmost portion of the hero stone slab has a depiction of four figures, three standing on foot and one mounted on a horse. This is a depiction of the ‘hero’ who embarked on an expedition, fought against enemies, and ultimately lost his life on the battleground. The erection of the hero stones is a tribute to honour his heroic deeds and sacrifice. He is also accompanied by some other figures, but the vermilion and oil make them difficult to identify. The three figures standing in front of the hero may represent celestial damsels who are shown bowing down to him. However, due to the presence of vermilion and oil on the stone, discerning their identities is challenging.